(3GdQCSeGdjI GdjghOjI hCKQgG Ydi GdMQcI GdUgjhfjI hGdJfXjeGJ GdTjhYjI (B1897-1937s - (3Ydj JSf(B, (3aQZdjs ((3GdEScfOQjI(B:s (3OGQ GdhaGA dOjfG ddWHGYI hGdfTQ(B,s, 2002)
(3GdQCSeGdjI GdjghOjI aj eUQ MJi (B1897- (3GdQCSeGdjI GdjghOjI aj eUQ aj eLGd GdHfhc hGdJLGQI hGdJCejf(B- (3GdQCSeGdjI GdjghOjI aj eUQ aj eLGd GdEfJGL hGdNOeGJ(B- (3CKQ GdQCSeGdjI GdjghOjI Ydi MjGI GdjghO GdELJeGYjI(B- (3CKQ GdQCSeGdjI GdjghOjI aj eUQ Ydi GdMQcI GdUgjhfjI(B- (3GdjghO hGdJfXjeGJ GdTjhYjI aj eUQs
Keywords: (3GdHfhc, GdJLGQI, eUQ, GdjghOs; (3GdQCSeGdjIs